Instrumented figure skating blade for measuring on-ice skating forces - Acuña, S. A.; Smith, D. M.; Robinson, J. M.; Hawks, J. C.; Starbuck, P.; King, D. L.; Ridge, S. T.; Charles, S. K. (Measurement Science and Technology, 2014)
Competitive figure skaters experience substantial, repeated impact loading during jumps and landings. Although these loads, which are thought to be as high as six times body weight, can lead to overuse injuries, it is not currently possible to measure these forces on-ice. Consequently, efforts to improve safety for skaters are significantly limited. Here we present the development of an instrumented figure skating blade for measuring forces on-ice. The measurement system consists of strain gauges attached to the blade, Wheatstone bridge circuit boards, and a data acquisition device. The system is capable of measuring forces in the vertical and horizontal directions (inferior-superior and anterior-posterior directions, respectively) in each stanchion with a sampling rate of at least 1000 Hz and a resolution of approximately one-tenth of body weight. The entire system weighs 142 g and fits in the space under the boot. Calibration between applied and measured force showed excellent agreement (R > 0.99), and a preliminary validation against a force plate showed good predictive ability overall (R= 0.81 in vertical direction). The system overestimated the magnitude of the first and second impact peaks but detected their timing with high accuracy compared to the force plate.